B-LMMSE-PIC iterative detection method for OTSM in high-speed mobile environment - LI Guojun; ZHENG Xiang; WANG Jie (Tongxin xuebao)
To improve the reliability of orthogonal time sequency multiplexing (OTSM) transmission in high-speed mobile environments, a block linear minimum mean square error with parallel interference cancellation (B-LMMSE-PIC) iterative detection method was proposed. The MMSE-PIC symbol estimation was performed in the time domain by block, and the Neumann series approximation was used for matrix inversion, which reduced the computational complexity to linear order. Subsequently, the mean and variance of the estimated symbols in the delay-sequency domain were calculated to provide prior information for the next iteration. Simulation results demonstrated that, under conditions of 540 km/h mobile speed and 16QAM modulation with a BER of 10-4, the proposed method achieves a performance gain of 2.48 dB compared to the widely used iterative rake detection algorithm based on maximum ratio combining (MRC).